Production of HIV-1 vif mRNA Is Modulated by Natural Nucleotide Variations and SLSA1 RNA Structure in SA1D2prox Genomic Region - Nomaguchi, Masako; Doi, Naoya; Yoshida, Tomoya; Koma, Takaaki; Adachi, Shun; Ode, Hirotaka; Iwatani, Yasumasa; Yokoyama, Masaru; Sato, Hironori; Adachi, Akio (Frontiers in Microbiology, 2017)
Genomic RNA of HIV-1 contains localized structures critical for viral replication. Its structural analysis has demonstrated a stem-loop structure, SLSA1, in a nearby region of HIV-1 genomic splicing acceptor 1 (SA1). We have previously shown that the expression level of vif mRNA is considerably altered by some natural single-nucleotide variations (nSNVs) clustering in SLSA1 structure. In this study, besides eleven nSNVs previously identified by us, we totally found nine new nSNVs in the SLSA1-containing sequence from SA1, splicing donor 2, and through to the start codon of Vif that significantly affect the vif mRNA level, and designated the sequence SA1D2prox (142 nucleotides for HIV-1 NL4-3). We then examined by extensive variant and mutagenesis analyses how SA1D2prox sequence and SLSA1 secondary structure are related to vif mRNA level. While the secondary structure and stability of SLSA1 was largely changed by nSNVs and artificial mutations introduced to restore the original NL4-3 form from altered ones by nSNVs, no clear association of the two SLSA1 properties with vif mRNA level was observed. In contrast, when naturally occurring SA1D2prox sequences that contain multiple nSNVs were examined, we attained significant inverse correlation between the vif level and SLSA1 stability. These results may suggest that SA1D2prox sequence adapts over time, and also that the altered SA1D2prox sequence, SLSA1 stability, and vif level are mutually related. In total, we show here that the entire SA1D2prox sequence and SLSA1 stability critically contribute to the modulation of vif mRNA level.